2014
DOI: 10.2337/db14-0190
|View full text |Cite
|
Sign up to set email alerts
|

Pregestational Diabetes Induces Fetal Coronary Artery Malformation via Reactive Oxygen Species Signaling

Abstract: Hypoplastic coronary artery disease is a congenital coronary artery malformation associated with a high risk of sudden cardiac death. However, the etiology and pathogenesis of hypoplastic coronary artery disease remain undefined. Pregestational diabetes increases reactive oxygen species (ROS) levels and the risk of congenital heart defects. We show that pregestational diabetes in mice induced by streptozotocin significantly increased 4-hydroxynonenal production and decreased coronary artery volume in fetal hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 50 publications
6
40
3
Order By: Relevance
“…Studies have shown that oxidative stress is a major driver of CHD pathogenesis . In our study, E14.5 embryonic hearts from the offspring of diabetic mice had significantly higher levels of superoxide and lipid peroxidation, an indicator of oxidative damage .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Studies have shown that oxidative stress is a major driver of CHD pathogenesis . In our study, E14.5 embryonic hearts from the offspring of diabetic mice had significantly higher levels of superoxide and lipid peroxidation, an indicator of oxidative damage .…”
Section: Discussionsupporting
confidence: 56%
“…AMIRA calculated the volume of the labelled components and these values were used to calculate the ratio of coronary artery volume to myocardial volume. 15,18…”
Section: Amira 3d Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus (DM) was induced by STZ injections . Specifically, female C57BL/6 mice (8 weeks old) were injected intraperitoneally with STZ (80 mg/kg body weight) for three consecutive days . At 1 week after the last injection, tail vein blood glucose concentration was measured with a glucose monitor (Roche, Mannheim, Germany) and DM was defined as a blood glucose level over 14 mmol/L (252 mg/dL) .…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies have shown that high blood glucose levels (>25 mmol/l) during pregnancy induced by STZ (80 mg/kg, i.p. for 3 days) result in CHDs in the offspring . In this study, a milder STZ dosing protocol (50 mg/kg i.p.…”
Section: Resultsmentioning
confidence: 95%